"And in that Dream, I Have Another Dream". Issue 6 (2nd November 2021) - Amir, Dana
ABSTRACT: My discussion of Roitman's paper focuses on the patient's refusal of the work of mourning, producing, instead, an idealizing, hermetic narrative which attacks any link with loss. This hermetic narrative leaves her trapped in a hollow territory in which language evacuates grief, or gets between her and her grief, rather than allowing contact with it. This also affects the therapeutic process, in which no vital link between therapist and patient, either, is allowed. The only way out of this grip is the therapist's willingness to give up symbolic/metaphoric interpretations for the sake of working on the level of metonymic interventions, or even surrendering to the psychotic level of pure enactment.